Species‐specific detection of Candida tropicalis using evolutionary conserved intein DNA sequences. (7th March 2018) - Rajasekharan, S.K.; Ray, A.K.; Ramesh, S.; Kannappan Mohanvel, S.
Abstract: Inteins (internal proteins) are self‐splicing transportable genetic elements present in conserved regions of housekeeping genes. The study highlights the importance of intein as a potential diagnostic marker for species‐specific identification of Candida tropicalis, a rapidly emerging opportunistic human pathogen. Initial steps of primer validation, sequence alignment, phylogenetic tree analysis, gel electrophoresis and real‐time polymerase chain reaction (PCR) assays were performed to confirm the specificity of the designed primers. The primers were selective for C. tropicalis with 100% inclusivity and showed no cross‐species or cross‐genera matches. The established technique is a prototype for developing multifaceted PCR assays and for point‐of‐care testing in near future. Significance and Impact of the Study: Development of molecular markers for specific detection of microbial pathogens using real‐time polymerase chain reaction (PCR) is an appealing and challenging technique. A real‐time PCR is an emerging technology frequently used to detect the aetiologic agents. In recent times, designing species‐specific primers for pathogen detection is gaining momentum. The method offers rapid, accurate and cost‐effective strategy to identify the target, thus providing sufficient time to instigate appropriate chemotherapy. The study highlights the use of intein DNA sequence as molecular markers for species‐specific identification of Candida tropicalis . The study also offers a prototype model for developing multifaceted PCR assays using intein DNA sequences, and provides a developmental starting point for point‐of‐care testing in near future. Abstract : Significance and Impact of the Study: Development of molecular markers for specific detection of microbial pathogens using real‐time polymerase chain reaction (PCR) is an appealing and challenging technique. A real‐time PCR is an emerging technology frequently used to detect the aetiologic agents. In recent times, designing species‐specific primers for pathogen detection is gaining momentum. The method offers rapid, accurate and cost‐effective strategy to identify the target, thus providing sufficient time to instigate appropriate chemotherapy. The study highlights the use of intein DNA sequence as molecular markers for species‐specific identification of Candida tropicalis . The study also offers a prototype model for developing multifaceted PCR assays using intein DNA sequences, and provides a developmental starting point for point‐of‐care testing in near future.